KONSTRUKSI KEGAGALAN IMUNISASI MR TAHAP KEDUA DALAM PEMBERITAAN MEDIA ONLINE - Haloho, Heppy N.Y (POPULIKA, 2020)
This research is intended to compare the construction of the failure of MR vaccine program in online news media (Republika online and Tempo.co) coverage. The paradigm used in this study is the constructivism paradigm with a qualitative approach. The method used in this research is the content analysis method using Robert Entman's framing device as a data analysis technique. The data in this study are news texts related to the failure of the coverage of the second phase of the MR vaccine program in Republika online and Tempo.co for the period September - November 2018. The results of this study indicate that in Tempo.co's framing, the failure of vaccine coverage was considered as a serious threat to the nation's safety due to the issuance of the illicit fatwa on MR vaccine by MUI, while in the Republika online’s frame, the issue was seen as an indication of low public awareness of health and is due to various factors such as very difficult geographical conditions, the threat of health workers and the illicit fatwa on MR vaccine by MUI.